Pembentukan Kepribadian Islami dalam Pendidikan Agama Islam - Ika Kurnia Sofiani; M Khairul Fadli; Indra Wahyu Saputra (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The formation of Islamic personality is a primary goal in Islamic education. Ethical education plays a crucial role in achieving this goal as it involves the moral and spiritual aspects of individuals. This research aims to analyze the Islamic perspective on ethical education and how it contributes to the formation of an Islamic personality. The methodology employed is a literature study involving the analysis of Islamic sources, including the Qur'an and Hadith. The analysis reveals that the Islamic approach to ethical education emphasizes the importance of good morals, social responsibility, and spiritual awareness. Islamic education should prioritize moral values such as honesty, justice, patience, and compassion. Additionally, education should encourage individuals to behave well and be responsible towards society, as well as develop spiritual awareness in their relationship with Allah. This research provides a deeper understanding of how ethical education, from an Islamic perspective, contributes to the formation of an Islamic personality.